The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/jcm.40.12.4729-4731.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Imported Malaria with the Cell-Dyn 4000 Hematology Analyzer

Abstract: The sensitivity and specificity of the Cell-Dyn 4000 hematology analyzer in the diagnosis of imported malaria were studied with samples from patients in an academic hospital setting. The performance of the Cell-Dyn 4000 hematology analyzer was compared with that of conventional diagnostic methods for malaria. The Cell-Dyn 4000 hematology analyzer detected hemozoin-containing depolarizing monocytes in 29 of 58 patients with malaria and 2 of 55 patients without malaria. The presence or absence of depolarizing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 4 publications
1
35
0
2
Order By: Relevance
“…7,8 Furthermore, because hemozoin in WBC seems to be a sensitive indicator of prognosis, an automated hematology analyzer may offer a new way to assess disease severity. 3 In this study, the mean difference in eosinophil counts between the Sysmex XE-2100 analyzer and microscopic examination was 16.0%, and the mean difference in neutrophil counts was 12.9%. This difference could be explained by the incorrect classification of hemozoin-containing neutrophils as eosinophils in malaria patients.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…7,8 Furthermore, because hemozoin in WBC seems to be a sensitive indicator of prognosis, an automated hematology analyzer may offer a new way to assess disease severity. 3 In this study, the mean difference in eosinophil counts between the Sysmex XE-2100 analyzer and microscopic examination was 16.0%, and the mean difference in neutrophil counts was 12.9%. This difference could be explained by the incorrect classification of hemozoin-containing neutrophils as eosinophils in malaria patients.…”
mentioning
confidence: 91%
“…Most reports are studies regarding abnormal depolarizing patterns of the Cell-Dyn hematology analyzer (Abbott Diagnostics, Santa Clara , CA). [1][2][3][4][5][6] Recent studies from South Korea investigated pseudoeosinophilia and abnormal white blood cell (WBC) scattergrams of vivax malaria-infected patients on a Sysmex XE-2100 hematology analyzer (Sysmex Corporation, Kobe, Japan). 7,8 Because the sensitivity and specificity of these methods were apparently high, its application to early detection can lead to a significant reduction in patients' morbidity and mortality.…”
mentioning
confidence: 99%
“…Recent studies using automated hematology analyzers have demonstrated unexpected abnormalities in differential white blood cell plots and reticulocyte histograms from patients with malaria. 6 In normal blood samples, the only depolarizing WBC events are eosinophils. With Cell-Dyn multiangle polarized scatter separation (MAPSS) analysis, normal eosinophils viewed in the polarized-90° versus depolarized-90° (NEU EOS) plot form a distinct cloud of events that are color coded green.…”
mentioning
confidence: 99%
“…One disadvantage of RDTs is that microscopy is needed to estimate the percent parasitemia and verify the species. There has been an increase in the number of automated hematology analyzers used for detection of malaria (13)(14)(15)(16)(17)(18) by flow cytometry methods. The sensitivity has ranged from 48 to 95% compared to microscopy.…”
mentioning
confidence: 99%
“…The reported sensitivity of microscopy ranges from 85% to 93% (7,8), with experienced microscopists being able to detect Ͻ100 to 500 parasites/l (7, 9). There have been diagnostic advances for malaria, including PCR (10), rapid diagnostic tests (RDTs) (11,12), and automated hematology analyzers (13)(14)(15)(16)(17)(18). PCR has a higher sensitivity than microscopy (100% versus 93%, respectively), with the ability to detect less than 5 parasites/l (8).…”
mentioning
confidence: 99%